Insights Into the Prognostic Value and Immunological Role of NAAA in Pan-Cancer - Da Huang; Jiayu Shen; Lingyun Zhai; Huanhuan Chen; Jing Fei; Xiaoqing Zhu; Jianwei Zhou (Frontiers in Immunology, 2022)
N-Acylethanolamine Acid Amidase (NAAA) is an N-terminal cysteine hydrolase and plays a vital physiological role in inflammatory response. However, the roles of NAAA in tumor immunity are still unclear. By using a series of bioinformatics approaches, we study combined data from different databases, including the Cancer Genome Atlas, the Cancer Cell Line Encyclopedia, Genotype Tissue-Expression, cBioPortal, Human Protein Atlas, TIMER, and ImmuCellAI to investigate the role of NAAA expression in prognosis and tumor immunity response. We would like to reveal the potential correlations between NAAA expression and gene alterations, tumor mutational burden (TMB), microsatellite instability (MSI), DNA methylation, tumor microenvironment (TME), immune infiltration levels, and various immune-related genes across different cancers. The results show that NAAA displayed abnormal expression within most malignant tumors, and overexpression of NAAA was associated with the poor prognosis of tumor patients. Through gene set enrichment analysis (GSEA), we found that NAAA was significantly associated with cell cycle and immune regulation-related signaling pathways, such as in innate immune system, adaptive immune system, neutrophil degranulation, and Toll-like receptor signaling pathways (TLRs). Further, the expression of NAAA was also confirmed to be correlated with tumor microenvironment and diverse infiltration of immune cells, especially tumor-associated macrophage (TAM). In addition to this, we found that NAAA is co-expressed with genes encoding major histocompatibility complex (MHC), immune activation, immune suppression, chemokine, and chemokine receptors. Meanwhile, we demonstrate that NAAA expression was correlated with TMB in 4 cancers and with MSI in 10 cancers. Our study reveals that NAAA plays an important role in tumorigenesis and cancer immunity, which may be used to function as a prognostic biomarker and potential target for cancer immunotherapy.